The biology of austroglanis gilli and austroglanis barnardi (siluriformes : austroglanididae) in the Olifants River system, South Africa - Mthombeni, Vusi Gedla (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2010)
Austroglanis gilli and A. barnardi are endemic to the Clanwilliam-Olifants System in the Western Cape, South Africa. The populations of each of these species are considered to be threatened by various anthropogenic activities, which include inappropriate agricultural practice and impacts of alien invasive fish species. The purpose of this thesis was to assess the life-history of these two endangered species in order to contribute to understanding their biology. Such information is vital for the development of strategies for their conservation. Marginal zone and marginal increment analyses from sectioned lapilliar otoliths of both A. gilli and A. barnardi showed a unimodal peak, suggesting a single annulus formation. The oldest specimens of A. gilli and A. barnardi were 12+ and 14+ years, respectively. The growth of A. gilli and A. barnardi was relatively slow and was best described by the von Bertalanffy growth curve as: L, = 131.56(1 - exp(- 0.27(t - 1.18 ))) for male and L, = 113.86(1 - exp(- 0.43(1- 0.74))) for female A. gilli from the Rondegat River. In the Noordhoeks River, growth was L, = 99.67(1 - exp(- 0.53(t - 0.35))) for male and L, = 96.60(1 - exp(- 0.64(t - 0.11 ))) for female A. gilli, and L, =71.02(1-exp(-0.26(1-3.07))) and L, = 69.50(1-exp(-0.36(1 - 1.88))) for male and female A. barnardi, respectively. The average natural mortality for the combined sexes was estimated using catch curve analysis at 0.37 ± 0.12 per year for A. gilli from the Rondegat River, and at 0.71 ± 0.05 and 0.39 ± 0.04 per year for A. gilli and A. barnardi from the Noordhoeks River, respectively. For A. gilli in the Rondegat River, the first maturity was estimated at 3.3 years (97.3 mm SL) for males and 3.1 years (94.3 mm SL) for females. In the Noordhoeks River, the first maturity for A. gilli was estimated at 2.0 years (71.9 mm SL) for males and 1.7 (66.4 mm SL) for females, and for A. barnardi at 2.0 (55.0 nun SL) for males and 2.9 years (58.9 mm SL) for females. Maturity corresponded closely to the asymptotic sizes from the von Bertalanffy curves, suggesting a shift in energy use from somatic growth to gonad development. Macroscopic assessment of the state of gonads, the Ganado-somatic index and histological examinations revealed that both A. gilli and A. barnardi have a single spawning season. The presence of oocytes in different stages of development in each of the ovaries of mature females collected between November and January suggested asynchronous, iteroperous serial spawning. The resorption of yolk was observed from ovaries collected between February and March and no vitellogenic oocyte was visible from ovaries collected between April and August. A similar trend was observed for males, with spermatozoa filling the lumen between November and January and some residual spermatozoa being present in the lumens soon after the breeding season. Spermatocytes and spermatids were dominant in the testes until October. An Index of Relative Importance revealed that A. gilli feeds predominantly on the benthic macroinvertebrate larvae of Ephemeroptera (particularly Baetidae), Diptera (particularly Chironomidae and Simuliidae) and Trichoptera. Austroglanis barnardi feeds predominantly on dipteran larvae (particularly Chironornidae and Simuliidae). Chi square contingency tables showed a significant difference in the dominant prey items of A. gilli and A. barnardi in the Noordhoeks River (X₂= 53.79, d.f. = 4, p > 0.001) and A. gilli between Rondegat and Noordhoeks rivers (x₂ = 34.74, d.f. = 4, p > 0.001). The Spearman's rank correlation test showed no shifts in the diet of A. barnardi from Noordhoeks River and A. gilli from Rondegat River with a change in size and season (p>O.OS). However, there was a shift in the diet of A. gilli from the Noordhoeks River which could suggest a distinct patchiness of benthic macroinvertebrates between the riffle feeding areas used by juveniles and other biotopes used by adults. The occurrence, in stomach contents, of other prey items from a wide variety of taxa and the presence of allochthonous material from the terrestrial environment could suggest an opportunistic feeding guild for both Austroglanis species. The life-history traits of A. gilli and A. barnardi, which are charaterized by slow growth, long life span and low relative fecundity, indicate that both species are relatively precocial and K-selected. The population of a precocial species is relatively stable and if population numbers were to be greatly reduced, they would require a long time to rebuild. An urgent conservation intervention is therefore recommended for Austroglanis spp. so as to maintain the diversity of populations within these species. The creation of protected river reserves and raising public conservation awareness may minimise activities that result in altered river hydrology and the destruction of complex benthic habitats.
Keywords: Catfishes -- South Africa -- Olifants River; Fishes -- South Africa -- Olifants River -- Growth; Freshwater fishes -- Effect of pesticides on -- South Africa -- Olifants River